Dispersion of SiC powder suspension in mullite sol and influence on properties of sintered ceramics. Issue 2 (9th October 2017) - Baitalik, Sanchita; Kayal, Nijhuma
Abstract: The dispersion behavior of SiC powders in various concentration of mullite sol was studied by zeta potential, rheological, and sedimentation measurements. Effect of pH, sol concentration, solid loading on the rheological properties are discussed in detail. The lowest viscosity and sedimentation was obtained for 45 wt% SiC powders dispersed in 15 wt% mullite sol, at pH ~2. The adsorption isotherms belong to Langmuir type and optimum concentration of mullite for maximum dispersion was found to be ~0.036 g/m 2 . The stabilization mechanism of SiC powder into mullite precursor sol was explained by Derjaguin‐Landau‐Vervey‐Overbeek (DLVO) theory. Coating was confirmed by transmittance electron microscopy and energy‐dispersive X‐ray spectroscopy analysis. Further sintering of the mullite‐coated SiC powder compact at 1300°C produced porous SiC ceramic with porosity ~40 vol% and pore diameter ~3 μm. The corrosion behavior of the ceramics was studied in strong acid medium at 90°C and compared with the ceramics obtained from uncoated SiC powder.